Clinical features of patients with acute kidney injury in dialysis in a general hospital - Herrera Añazco, Percy (2013)
Introduction: Acute kidney injury on dialysis has high mortality in hospitalized patients especially in ICU and there are no updatedstudies in our country. Objectives: To describe characteristics of acute kidney injured patients on dialysis at a general hospital. Design:Descriptive single center observational study. Setting: Hospital Nacional Dos de Mayo, Lima, Peru. Patients: Acute kidney injured (AKI)patients on dialysis. Interventions: We studied patients with AKI on dialysis from January to December, 2012. We described averages,percentages, standard deviations. Main outcome measures: Clinical characteristics of patients with AKI on dialysis. Results: Forty-threeacute kidney injured cases on dialysis were reported. Average age was 58.5 years (SD: 16.6), 28 were male, 20 patients (46.5%) werefrom ICU. The main cause of dialysis admission was oligoanuria (60.5%) followed by uremic encephalopathy (46.5%) and metabolicacidosis (30.2%); 39.5% patients died; 45% of patients in ICU died. At hospital discharge 9.3% of the patients continued on dialysis.Conclusions: In the population studied 4 of 10 patients with acute kidney injury on dialysis died and 1 of 10 patients continued ondialysis after hospital discharge.